2009
DOI: 10.1007/s11295-009-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus (QTL) analysis of wood quality traits in Eucalyptus nitens

Abstract: To identify the chromosomal regions affecting wood quality traits, we conducted a genome-wide quantitative trait locus (QTL) analysis of wood quality traits in Eucalyptus nitens. This information is important to exploit the full potential of the impending Eucalyptus genome sequence. A three generational mapping population consisting of 296 progeny trees was used to identify QTL associated with several wood quality traits in E. nitens. Thirty-six QTL positions for cellulose content, pulp yield, lignin content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 47 publications
4
64
0
Order By: Relevance
“…Recent QTL studies, however, have reported a substantially larger number of QTLs for wood quality traits whose effects estimated rarely exceed 5%. Thumma et al (2010) detected 36 QTLs for cellulose content, pulp yield, lignin content, density, and microfibril angle (MFA) in E. nitens. Gion et al (2011) described a total of 117 QTLs for a number of wood and end-use related traits, including chemical, technological, physical, mechanical and anatomical properties.…”
Section: Next-generation Sequencing Resourcesmentioning
confidence: 99%
“…Recent QTL studies, however, have reported a substantially larger number of QTLs for wood quality traits whose effects estimated rarely exceed 5%. Thumma et al (2010) detected 36 QTLs for cellulose content, pulp yield, lignin content, density, and microfibril angle (MFA) in E. nitens. Gion et al (2011) described a total of 117 QTLs for a number of wood and end-use related traits, including chemical, technological, physical, mechanical and anatomical properties.…”
Section: Next-generation Sequencing Resourcesmentioning
confidence: 99%
“…The characterization of natural genetic perturbations segregating in phenotypically wild-type individuals offers an attractive alternative tool to study properties that emerge from permissible genetic variation (11,13). With the availability of high-throughput genotyping and high-resolution linkage maps in Populus (14,15) and Eucalyptus (16)(17)(18)(19), genetic approaches such as quantitative trait locus (QTL) (14,20,21) and LD-based association mapping (22)(23)(24)(25) are becoming feasible to…”
mentioning
confidence: 99%
“…In another study, the high yield of pulp and cellulose content was associated with the low content of extractives and total lignin (Poke et al, 2006). For Eucalyptus nitens, Kube et al (2001) found a high negative genetic correlation between extractive content and cellulose, which was the same correlation found by Thumma et al (2010) in the study of wood quality with QTLs for the same species. Together, these studies suggest that selection to increase the yield of pulp or cellulose content would probably result in the reduction of lignin and extractive content, which is a favorable for the production of wood for the pulp industry (Poke et al, 2006).…”
Section: Proteomic Characterization Of Eucalyptus Clonesmentioning
confidence: 73%